Energieffektiv produktion och lagring av snö för skidtunnel : Utredning för applicering vid Lindbäcksstadion, Piteå - Fröjd, Henrik (2014)
Today, there is a seldom seen interest for cross-country skiing. However, the winters are getting warmer, which causes lack of snow and hence a shortened skiing season. In order to solve this problem the company Lindbäcks Bygg plans to construct a ski tunnel at Lindbäcksstadion close to Piteå. At the request of this company, this master thesis aims to investigate different methods for an energy efficient supply of the tunnel’s snow demand. The main part of this project has considered design of systems for snow production and snow storage. Four different alternatives for the supply of snow to the tunnel have been investigated: outdoor storage and production of artificial snow, storage of natural snow and production of snow directly inside the ski tunnel or an external facility. These methods have been compared regarding energy consumption, costs and operation-related environmental impact in the terms of greenhouse gas emissions. It was found that the energy consumption was significantly higher for indoor than outdoor snow production, mainly because of the energy required for removal of the heat emitted when the water supplied to the snow gun changes phase into ice. The energy demand for storage and production of artificial snow was determined to 8.5 MWh, which is equivalent to the demand for storage and transport of natural snow. The corresponding values for snow production inside the ski tunnel and the external production facility were calculated to 1.5 and 1.1 GWh respectively. From an economic perspective, outdoor snow production is also preferable. The highest investment cost is to be found for the external production facility. The operating costs are however higher for snow production inside the ski tunnel and notably lower for the two snow storage alternatives. The environmental impact related to operation is very low for all the alternatives, provided that the electricity demand is supplied by renewable sources. The highest greenhouse gas emissions are related to the transport and storage of natural snow. ...